Application of Workshop Techniques to Improve Teacher Pedagogic Competence in Making Power Point Projection Media at SLB PAB Payakumbuh - Syaflinda, Syaflinda; Nazri, Ismail (International Journal of Education and Digital Learning (IJEDL), 2022)
This research was conducted at SLB PAB Payakumbuh City in the odd semester of the 2022/2023 school year to describe the Application of Workshop Techniques to Improve Teacher Pedagogic Competence in Making Power Point Projection Media at SLB PAB Payakumbuh. Power point projection media is ICT-based learning media that can be used to motivate students in learning because it can be filled with media images, videos and animations. The findings in the study at Payakumbuh PAB SLB were that there was an increase in the pedagogic competence of individual teachers from 61.6% pre-cycle activities to 72.5% in cycle I and 82.5% in cycle II. In addition, mastery of the media component of power point projection was also experienced an increase from 61.6% in pre-cycle activities to 76.2% in cycle I and experienced a significant increase of 87